Non-obese non-alcoholic fatty liver disease and the risk of chronic kidney disease: a systematic review and meta-analysis - You,Yixian; Pei,Xiong; Jiang,Wei; Zeng,Qingmin; Bai,Lang; Zhou,Taoyou; Lv,Xiaoju; Tang,Hong; Wu,Dongbo (PeerJ, 2024)
Background Data on risk of developing chronic kidney disease (CKD) between non-obese and obese non-alcoholic fatty liver disease (NAFLD) patients are limited. We aimed to reveal the risk difference of incident CKD between non-obese and obese NAFLD patients. Methods We searched PubMed, Embase, and Web of Science databases for studies which reported the incidence of CKD in non-obese and obese NAFLD from inception to 10 March 2024. The primary and secondary outcomes were pooled. Subgroup analysis was used to examine the heterogeneity. Results A total of 15 studies were incorporated. The incidence of CKD in non-obese and obese NAFLD were 1,450/38,720 (3.74%) and 3,067/84,154 (3.64%), respectively. Non-obese NAFLD patients had a comparable risk of CKD as obese NAFLD (odds ratio [OR] 0.92, 95% confidence interval [95% CI] [0.72–1.19], I2 = 88%). No differences in estimated glomerular filtration rate and serum creatinine between non-obese and obese NAFLD were found. The mean differences (MD) and 95% CI were 0.01 [−0.02 to 0.04] and 0.50 [−0.90 to 1.90], respectively. In subgroup analyses, non-obese NAFLD had higher eGFR when diagnosed with ultrasound (MD 1.45, 95% CI [0.11–2.79], I2 = 21%). Non-obese NAFLD had higher creatinine in non-Asian (MD 0.06, 95% CI [0.01–0.11], I2 = 55%) and when taking BMI > 30 as the criterion for obesity (MD 0.06, 95% CI [0.00–0.12], I2 = 76%). The occurrence of CKD did not differ when non-obese NAFLD were categorized into overweight and normal-weight types. Conclusions Non-obese NAFLD patients experienced the same risk of CKD compared to obese NAFLD.
Keywords: NAFLD; CKD; Non-obese; eGFR; Creatinine